SAT0208 Seven-Joint Power Doppler Ultrasound Score is Discordant to DAS28, SDAI and CDAI in Treatment Target Identification in Rheumatoid Arthritis Patients with Fibromyalgia. (10th June 2014) - Chakr, R.; Behar, M.; Mendonça, J.A.; Moro, A.L.; Zanchet, D.; Siqueira, I.; Hax, V.; Gasparin, A.; Palominos, P.; Kohem, C.; Brenol, C.; Monticielo, O.; et al.
Abstract : Background: FM increases DAS28, SDAI and CDAI, misleading DMARD use and increasing costs and adverse events. (1, 2) Seven-joint PDUS score is an objective measure of RA activity and, therefore, should not be influenced by FM. (3) Objectives: To compare 7-joint PDUS score, DAS28, SDAI and CDAI as instruments to identify treatment target in RA patients with and without FM. Methods: A transversal case-control study matched by RA duration and rheumatoid factor positivity was conducted from March 2012 through March 2013. Cases were RA patients with FM and controls were RA patients without FM, according to ACR classification criteria for RA (1987) and FM (1990). Cases and controls were consecutively recruited from a University-based RA clinic. DAS28, SDAI, CDAI and 7-joint PDUS scoring was blinded. Target discordance was defined as moderate or high disease activity in DAS28, SDAI or CDAI and a joint-level PDUS score ≤1. Medians (IQR) were compared by Mann-Whitney's test. Two-tailed P values <0.05 were considered significant. OR (95%CI) of RA target discordance due to FM was calculated for DAS28, SDAI and CDAI. Results: Seventy-two RA women were included (36 with FM and 36 without FM). Median (IQR) age was 57.5 (49.3-66.8) years, RA duration was 13.0 (6.0-19.0) years and FM duration was 6.0 (2.0-15.0) years. Cases (RA with FM) and controls (RA without FM) had similar 7-joint PDUS scores 3.0 (1.0-5.8) vs. 4.0 (2.0-5.0), P=0.87, respectively. Cases had greater DAS28 [4.6 (3.3-5.8) vs. 3.3 (2.7-4.0), P<0.001], SDAI [15.9 (10.7-28.9) vs. 8.3 (5.0-13.1), P<0.001] and CDAI [15.3 (10.1-28.4) vs. 8.0 (4.2-12.9), P<0.001] than controls. Cases and controls with DAS28-derived target discordance were 23 (64%) and 14 (39%), respectively [OR 2.8 (1.1-7.2)]. Cases and controls with SDAI-derived target discordance were 20 (56%) and 9 (25%), respectively [OR 3.8 (1.4-10.2)]. Cases and controls with CDAI-derived target discordance were 21 (58%) and 9 (25%), respectively [OR 4.2 (1.5-11.5)]. Conclusions: The distortion of clinical RA treatment target caused by concomitant FM may be attenuated by 7-joint PDUS scoring. Longitudinal studies comparing 7-joint US score, DAS28, SDAI and CDAI are needed to demonstrate if an objective target improves RA treatment outcomes, by preventing overtreatment and decreasing adverse events and costs. References: Arthritis Rheum. 2009 Jun 15;61(6):794-800 J Rheumatol. 2013 Dec;40(12):1977-85 Arthritis Rheum. 2009 Sep 15;61(9):1194-201 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3306